Implementasi Teknologi Enterprise Resource Planning dan Digital Supply Chain dalam Manajemen Operasi Samsung Electronics - wahyu nugroho (Jurnal Manajemen Dayasaing, 2026)
Digital transformation has become a crucial factor in enhancing operational efficiency and competitiveness for global companies. This study analyzes the implementation of Enterprise Resource Planning (ERP) and Digital Supply Chain Management (SCM) by Samsung Electronics through Samsung SDS services. Enterprise Resource Planning (ERP) enables cross-functional business process integration, operational automation, and real-time data availability, reducing data duplication and improving decision-making. Next-generation Digital Suplly Chain Management, leveraging AI, RPA, and cloud platforms, supports scenario-based planning, rapid response to supply chain disruptions, and enhanced visibility and coordination across operations. The integrated implementation of Enterprise Resource Planning (ERP) and Digital Suplly Chain Management improves productivity, flexibility, cost efficiency, and innovation, while strengthening Samsung Electronics’ competitive position in the global market. The findings highlight the strategic importance of digital technology adoption in operations management for sustaining competitive advantage and corporate sustainability.